Developing PISA-like math problems in the content of space and shape through the context of historical buildings - Aini, Indrie Noor; Zulkardi; Putri, Ratu Ilma Indra; Yaniawati, Poppy (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
The essential purpose of developing PISA-like questions is to train students' reasoning abilities so that students' ability to solve PISA-like questions increases. Therefore, this research aims to produce PISA-like math problems in the context of historical buildings in the Karawang Regency that are valid, practical, and potentially affect mathematics learning. The subjects of this study were junior high school students at SMPN 2 Karawang Barat. This research uses design research with development studies, consisting of preliminary and prototyping phases. The preliminary stage consists of two stages: needs analysis and design, while the prototyping stage consists of 5 phases: self-evaluation, expert review, one-to-one, small group, and field tests. The data collection techniques in this study were in the form of PISA-like math problems in the context of shape and space with the context of Historic Buildings in Karawang, observations, questionnaires, and interviews. All data obtained were analyzed descriptively. The results show that this study resulted in nine PISA-like math problems in the context of shape and space with the context of Historic Buildings in Karawang that are valid, practical, and potentially affect learning mathematics. The potential effect is related to students' interest in PISA-like questions and students' ability to understand and answer PISA-like questions. Finally, the results of this study have an impact on students who are getting trained in solving PISA-like math problems.